Historical blocking: CN 2022-05-23 to 2022-05-26 (China) - Voidly (2022)
CRITICAL severity censorship detected in China. Confidence: 93%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2022-0336
Keywords: censorship; CN; censorship; critical